Project Analysis for Development Telkom University Dormitory as A Support Facility - Putri, Dwi Kurnia; Surya, Budhi Arta (The Indonesian Journal of Business Administration, 2014)
Abstract. World Class University is considered as a way of a Telkom University to be able compete in this globalization era. One of the supporting facilities to achieve goal of becoming the World Class University is providing the student dormitories. Dormitory can be a place for learning activities, socialize, and discuss, which is expected to increase student motivation to more achievement and beneficial to the world. Feasibility study is require to determine whether the investment is worth to executed and to convince the investors. It can be viewed from a variety of indicators such as PBP, NPV, IRR, ROI, and ROE. Next analysis is to perform a sensitivity analysis to see the effect of changing the volatile variable (inflation, revenue, proportion of debt, labor costs, and interest rates) to financial indicators such as NPV and optimal analysis to obtain the minimum number of dormitory occupants and minimum rental price dormitory that the project still feasible. Based on the results, the construction of student dormitories investment is feasible. The feasibility analysis generates a value of PBP 2 years 4 days, NPV Rp. 35,959,231,012, IRR 52.43%, ROI 13.93%, and ROE 39.79%. Sequentially, the variables that influence the change in NPV is inflation, revenue, proportion of debt, labor costs, and interest rates. Minimum number of dormitory occupied is 82% or 1542 students and minimum rental price dormitory is Rp. 5,200,000 per year. Implementation of this dormitory building process starts from feasibility analysis, bank selection and loan process, contractor selection, and process construction includes build structures, architectural, mechanical and electrical. This dormitory construction project can be completed within 16 months. Recommendation for this project, to increase the value of NPV, the company must have the ability to well negotiate with the investor in order to get maximum the proportion of debt, because of the cost of debt for the project is lower than the cost of equity.Keywords : Dormitory, NPV, IRR, sensitivity, optimal